Multi‐model and multi‐scenario assessments of Asian water futures: The Water Futures and Solutions (WFaS) initiative. Issue 7 (28th July 2017) - Satoh, Yusuke; Kahil, Taher; Byers, Edward; Burek, Peter; Fischer, Günther; Tramberend, Sylvia; Greve, Peter; Flörke, Martina; Eisner, Stephanie; Hanasaki, Naota; Magnuszewski, Piotr; Nava, Luzma Fabiola; et al.
Abstract: This paper presents one of the first quantitative scenario assessments for future water supply and demand in Asia to 2050. The assessment, developed by the Water Futures and Solutions (WFaS) initiative, uses the latest set of global climate change and socioeconomic scenarios and state‐of‐the‐art global hydrological models. In Asia, water demand for irrigation, industry, and households is projected to increase substantially in the coming decades (30–40% by 2050 compared to 2010). These changes are expected to exacerbate water stress, especially in the current hotspots such as north India and Pakistan, and north China. By 2050, 20% of the land area in the Asia‐Pacific region, with a population of 1.6–2 billion, is projected to experience severe water stress. We find that socioeconomic changes are the main drivers of worsening water scarcity in Asia, with climate change impacts further increasing the challenge into the 21st century. Moreover, a detailed basin‐level analysis of the hydro‐economic conditions of 40 Asian basins shows that although the coping capacity of all basins is expected to improve due to gross domestic product (GDP) growth, some basins continuously face severe water challenges. These basins will potentially be home to up to 1.6 billion people by mid‐21st century. Key Points: A first assessment of Asian water futures using multi‐model and multi‐scenario approach 1.6–2 billion people are projected to experience severe water stress conditions in Asia by 2050 Socioeconomic changes have critical impacts on water security and are found to be a main driver of growing water scarcity in Asia Plain Language Summary: Home to almost 4.5 billion people, Asia has experienced unprecedented economic and population growth in recent decades. In order to sustain growing food demand and increasing standard of living, water use has been increasing rapidly in many parts of Asia. At present, water withdrawals in Asia represent 65% of the global total. This huge abstraction of water resources has resulted in many Asian regions undergoing pervasive water scarcity conditions. The imminent global changes from climate change and socioeconomic development in Asia are expected to place additional pressures on water resources in the coming decades. In such a context, it is imperative to evaluate future water scarcity conditions and identify regions at highest risk in Asia. We found that by 2050, 20% of the land area in Asia, with population exceeding 1.6–2.0 billion, is projected to experience severe water scarcity. Here, we for the first time highlight that socioeconomic changes are the main driver of worsening water scarcity in Asia, much larger than the climate change impacts.